Study on the Changes of Structures and Properties of PAN Fibers during the Cyclic Reaction in Supercritical Carbon Dioxide - Qiao, Mengmeng (Polymers (Basel), 2019)
Thermal pre-oxidation of polyacrylonitrile (PAN) fibers is a time-consuming and energy-consuming step in the production of PAN-based carbon fibers. In this paper, the effect of temperature on the structures and properties of PAN fibers cyclized in the supercritical carbon dioxide (Sc-CO(2)) medium was studied. The thermal behaviors of the PAN fibers were investigated by Fourier transform infrared spectra (FT-IR), X-ray diffraction (XRD), differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA). The cyclization reaction was sensitive to the heating temperature and gas atmosphere. The FT-IR results of the PAN fibers treated in the Sc-CO(2) confirmed that the degree of cyclization increased with the increase of the cyclization temperature. Compared with the PAN fibers treated in the air, the PAN fibers treated in the Sc-CO(2) showed a higher degree of cyclization even at the same temperature. These findings might be related to the osmotic action of Sc-CO(2) causing the fibers to be further arranged in a regular manner, which was favorable for the cyclization reaction. Moreover, as one kind of high diffusion and high heat transfer media, the heat release during the cyclization of PAN fibers could be quickly removed by Sc-CO(2), which achieved the progress of the rapid-entry cyclization reaction.